FREQUENCY OF IRRITABLE BOWEL SYNDROME IN COLLEGE STUDENTS - Jafri, Wasim; Yakoob, Javed; Jafri, Nadim; Islam, Muhammad; Ali, Qazi Masroor (Journal of Ayub Medical College Abbottabad, 2005)
Background: This study was carried out to investigate the presence of irritable bowel syndrome (IBS) in college students and compare its distribution in the non-medical college and medical college students. Methods: We collected data from 508 students by inviting them to fill out a questionnaire based on Rome II criteria for the diagnosis of IBS from November 2001 to February 2004. Two major cities Karachi and Bahawalpur were selected and it was coordinated by the section of Gastroenterology, Department of Medicine, Aga Khan University Hospital and Quaide-Azam Medical College, Bahawalpur. Results: A total of 508 subjects with males 43 % (220/508) and female 57 % (288/508) mean age 22 ± 2.8 years responded to the questionnaire. The overall frequency of IBS among college students was 34 % (171/508).There were 41 % (107/263) non-medical college and 26 % (64/245) medical college students with IBS. Abdominal pain was present in 100 % (171/171) with altered frequency of stool in 58 % (100/171) (p< 0.001, OR 12.5, CI 7.9-20.0) of students with IBS. The medical advice was sought by 38 % (65/171) in IBS group with 46 % (30/65) non-medical college school and 54 % (35/65) medical student (p=0.001, OR 1.9, CI 1.3-2.8). Conclusion: IBS is common in younger adult population of Pakistan. Its prevalence is higher in non-medical college students but health care seeking behavior was more common in medical students. Key words: Irritable Bowel Syndrome students, youngs, health seeking behavior